ANALISIS PENGARUH PENGGUNAAN APLIKASI SIMGAJI WEB TASPEN TERHADAP PENGURANGAN KESALAHAN PEMBAYARAN TUNJANGAN KELUARGA ASN DENGAN KEDISIPLINAN SEBAGAI VARIABEL MEDIASI - Yunita Wibawani; Martaleni; Djuni Farhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the use of the SIMGAJI Web Taspen application on reducing errors in family allowance payments for Civil Servants (ASN), with discipline as a mediating variable. The background of this research is based on the continued occurrence of payment errors despite the implementation of a digital payroll system in the Government of Probolinggo Regency.This research employs a quantitative approach using a survey method involving 54 payroll treasurers from Regional Apparatus Organizations (OPD). Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) to examine the relationships between variables.The results show that the use of the SIMGAJI Web Taspen application has a positive and significant effect on reducing errors in family allowance payments. In addition, the use of the application also positively influences the level of ASN discipline. ASN discipline is proven to have a significant effect on reducing payment errors and also acts as a mediating variable in the relationship between application usage and the reduction of payment errors. The R² values of 0.49 for discipline and 0.587 for the reduction of payment errors are both categorized as moderate, indicating that the model has sufficient explanatory power for the relationships among variables.These findings indicate that the success of information system implementation is not only determined by technology but also by user behavior, particularly discipline in data management. Therefore, improving the quality of application usage should be accompanied by strengthening ASN discipline to minimize payment errors and enhance payroll accuracy.